ANALISIS STABILITAS LERENG PADA PIT TAMBANG AIR LAYA BARAT SECTION C-C’ PT BUKIT ASAM (PERSERO) TBK., SUMATERA SELATAN - M Adli Fikri; Bambang Heriyadi; Heri Prabowo (Departemen Teknik Pertambangan FT UNP, 2018)
Mining is an activity that starts from the general investigation activities of minerals and coal. Mineral and coal mining activities in open space in the form of excavation and stockpiling will always face the problems of slope stability. Slope stability is a vital factor in the planning and operation of open pit and quarry mines. The occurrence of landslide in cross section of C-C' pit of Tambang Air Laya Barat of PT Bukit Asam (Persero) Tbk. causes this analysis to be done.This research is applied research with quantitative method. Slope stability analysis is assisted by Geostudio 2018 Slope/W trial licence 30 days version. The analysis of safety factor was done by Janbu Method. The data used are secondary data consisting of physical and mechanical parameter data of soil and rock, data of type and condition of soil and rock layout, design of mining pit plan, cross section of pit mining data, and data value of regional seismic constant.The results showed that the lowest actual value of slope safety factor was in the overall slope of low wall elevation +65 to -21 ie 0.966. Based on the analysis of data confidence increase, the overall slope on low wall is in unsafe condition, that is, single slope +57 to +13 with FK = 1.165, intermediate slope +65 to +14 with FK = 1.030, and overall slope of elevation +65 to -21 with value FK = 0.812 (FK <1.25). Based on back analysis, safety factor of single slope of +57 to +13 is 0.902, safety factor of intermediate slope is 0.747, safety factor of overall slope is 0.736. The most optimal of slope redesign recommendation is the forward-analysis method of the back-end analysis by the Hoek & Bray method. The slope recommendation is to change the geometry of the slope with the angle 19o to 11o and change the height from 85m to 76m. The single slope of the elevation +57 to +13 initially made only one single slope converted into three single slopes with each elevation +55 to +42, +42 to +29, +29 to +13.Keyword: slope stability analysis, safety factor, confidence level